The UK as a Destination Choice for Chinese Tourists: An Analysis of Tourist Motivation Factors - Zhang, Ling (2006)
With a population of over 1.3 billion and a rapidly expanding economy, the Peoples Republic of China has the potential to exert greater influence over the development of tourism worldwide over the next decade than perhaps any other country (King, 2003). Currently the UK accounts for merely 0.6% of all outbound trips from China (visitBritain.com, 2006). To explore in Chinas outbound travel market for UK, the examination of tourist motivation factors in Chinese context is necessary to see whether they are playing roles in motivating Chinese tourists to travel to the United Kingdom, for it is believed that tourist motivation is the driving force behind all tourist behaviours including destination choice (e.g., Mayo and Jarvis, 1981; Jamrozy and Uysal, 1994).